Measuring efficiency of just in time implementation using a fuzzy data envelopment analysis approach: real case of Iranian dairy industries. (1st January 2011) - Khalili-Damghani, Kaveh; Abtahi, Amir-Reza
In this paper, a procedure based on data envelopment analysis has been developed to measure the efficiency of complicated process in which just in time (JIT) practices transformed into operational and firm performance indices. A given organisation has been associated with a decision making unit (DMU) in which JIT practices are assumed to be inputs and operational and firm performance indices are considered. The fuzzy sets have been selected to measure the vague nature of JIT practices and performance indices. The proposed fuzzy DEA caused proper reduction in computational efforts. Real case study of Iranian dairy industry, as a proper testimonial in which high level of JIT practices play essential role, has been supplied to investigate the robustness of proposed approach.